Handbook of critical theory (Blackwell, 1996)
This book is divided into seven parts: Philosophy and history; Social science, discourse ethics, and justice; Law and democracy; Civil society and autonomy; Pragmatics, psychoanalysis, and Aesthetics; Postmodernism, critique, and the pathology of the social; Bibliography.